2009
DOI: 10.1080/10428190902803669
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood Epstein-Barr virus DNA load as a diagnostic and prognostic surrogate: extranodal natural killer/T-cell lymphoma

Abstract: We investigated the value of Epstein-Barr virus (EBV) DNA load in unfractionated whole blood for the diagnosis and prognosis of EBV-associated lymphoma. From July 2004 to July 2007, we compared EBV DNA loads in 101 patients with lymphoma and 105 control individuals. The median copy number of EBV was higher in patients with EBV-positive lymphoma (p<0.001). In patients with natural killer (NK)/T-cell lymphomas, the median EBV DNA load at presentation was significantly related to the stage (p = 0.011) and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 24 publications
6
44
3
Order By: Relevance
“…[22][23][24][38][39][40][41] Several small cohort of studies have demonstrated that a high EBV-DNA load is associated with advanced stage, poor clinical response, B-symptoms, and elevated LDH levels in NKTCL (supplemental Table 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). [31][32][33][34][35] Our results confirmed that pretreatment EBV-DNA levels correlate with B-symptoms, elevated LDH levels, and an IPI score of 1-2 in early-stage NKTCL. Interestingly, the median concentrations of EBV-DNA (491 copies/mL) in this series were similar to previous studies in low-risk patients who presented with early-stage disease, in which EBV-DNA was detected at relatively low levels (median, 349 or 659 copies/ mL).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…[22][23][24][38][39][40][41] Several small cohort of studies have demonstrated that a high EBV-DNA load is associated with advanced stage, poor clinical response, B-symptoms, and elevated LDH levels in NKTCL (supplemental Table 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). [31][32][33][34][35] Our results confirmed that pretreatment EBV-DNA levels correlate with B-symptoms, elevated LDH levels, and an IPI score of 1-2 in early-stage NKTCL. Interestingly, the median concentrations of EBV-DNA (491 copies/mL) in this series were similar to previous studies in low-risk patients who presented with early-stage disease, in which EBV-DNA was detected at relatively low levels (median, 349 or 659 copies/ mL).…”
Section: Discussionsupporting
confidence: 74%
“…31,33 Preliminary results in a small cohort of NKTCL patients have shown that patients with high concentrations of pretreatment EBV-DNA and detectable EBV-DNA levels after treatment have an extremely poor survival rate. [31][32][33][34][35] In this large series of early-stage patients with a favorable prognosis, a survival difference in patients with various EBV-DNA loads was also observed. The pretreatment EBV-DNA level of Յ 500 copies/mL and undetectable EBV-DNA levels after treatment predicted better survival rates in patients with early-stage NKTCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The test used hybridization probes to detect a gene fragment encoding a single copy of the EBV gene EBNA 1. The primers and probes in the kit were specific for amplifying and detecting the EBV DNA.…”
Section: Treatmentmentioning
confidence: 99%